Foucault as Translator of Binswanger and von Weizsäcker. (January 2023) - Elden, Stuart
Foucault's Introduction to a translation of Ludwig Binswanger's essay 'Dream and Existence' was published in late 1954. The translation was credited to Jacqueline Verdeaux, with Foucault acknowledged for the notes. Yet Verdeaux herself indicates the intensely collaborative nature of their working process and the translation. In 1958, Victor von Weizsäcker's Der Gestaltkreis was published in French as Le Cycle de la structure, translated by Foucault and Daniel Rocher. Foucault went on to translate and introduce Immanuel Kant's Anthropology as his secondary doctoral thesis. His engagement with Kant and Binswanger's ideas has been discussed in the literature, but his role as translator has generally been neglected. His engagement with von Weizsäcker is almost never mentioned. This article critically discusses Foucault's role in the Binswanger and von Weizsäcker translations, comparing the German originals with the French texts, and showing how this is a useful additional element to the story of the early Foucault.